Long-term survival in a patient with low-level inflammatory markers and liver metastasis, converted resectable by TACE. (October 2017) - Mizandari, Malkhaz; Paksashvili, Natela; Kikodze, Nino; Azrumelashvili, Tamta; Pantsulaia, Ia; Shanava, Koba; Janikashvili, Nona; Chikovani, Tinatin
Case report presents the successful treatment of unresectable liver metastasis in a patient with colon cancer. A 44-year-old male underwent right hemicolectomy followed by capecitabine for a moderately differentiated adenocarcinoma of the colon. 2 years later, a liver metastatic lesion was detected and had increased in size despite chemotherapy with capecitabine plus oxaliplatin (XELOX). Curative liver resection was conducted after conversion of unresectable tumor to resectable by transarterial chemoembolization followed by chemotherapy – irinotecan with fluorouracil and folinic acid (FOLFIRI). No recurrence was observed during 22-month follow-up after hepatectomy.